Hubungan antara motivasi, gaya pembelajaran dengan pencapaian matematik tambahan pelajar tingkatan 4 - Norlia Abd. Aziz,; T. Subahan M. Meerah,; Lilia Halim,; Kamisah Osman, (penerbit ukm, 2006)
The aim of the study is to determine the relationship between motivation, learning style and achievement in Additional Mathematics of Form 4 students.The study also aims to identify the different learning styles based on gender, ethnicity and students’ prior achievement in Additional Mathematics. A survey was carried out on 350 Form 4 students from four secondary schools in Kuala Terengganu. The instrument used was Studying At School Inventory by Selmes (1987) which postulated four learning styles namely deep, surface, organized and hard work. The fifth learning scale was adapted to measure only internal and external motivation. Data gathered were analyzed descriptively and inferentially using the SPSS package. Results from the descriptive analysis found that the students showed high internal motivation orientation and employed surface learning and deep learning styles as compared to organized and hard work learning styles. Results from the inferential analysis showed that there was a relationship between achievement in Additional Mathematics and deep, hard work and organized learning styles. In addition there is a significant relationship between internal motivation orientation and deep learning style. Findings from the study showed that there was no significant difference in learning styles based on gender, ethnicity and prior achievement. The implication of the study was that, motivation plays an important role in determining students’ choice of learning styles.